Národ jako kulturní konstrukt? - Hroch, Miroslav (Lidé města, 2005)
During the past decade there is a growing number of researchers that approach nation as a “Cultural construct” or even as “Erfundene Gemeinschaft”. Instead of studying the question of program, social basis or organizational forms, growing number of new publications focus on research of national symbols, commemorations, myths – and role of women in national movements. Instead of the question WHY?, the question HOW? becomes more prevalent. Stated more precisely, instead of search for chain of causation in world of objective “outer” relationships, these connections are searched for in the “inner” world of actors who are, on numerous occasions, regarded as “creators” of a nation. This is implicitly based on a notion that forms of national life, same as the idea of a nation, were present at a cradle of national subjects. Explicitly, the role of irrational factors as opposed to rational ones is stressed; feeling against intellect.